Thermal analysis of FeCoCu pre-alloyed powders used for diamond tools - Delong Xie; Leyin Xiao; Feng Lin; Xiaoyi Pan; Yu Su; Xiaohu Fang; Haiqing Qin; Chao Chen (Сверхтвердые материалы, 2018)
By simulating the pressureless sintering process, the thermal effects of FeCoCu pre-alloyed powders have been investigated. According to the notions of the Kissinger method, the activation energies in the expansion-shrinkage conversion stage are analyzed. Results show that with Fe content increasing, the specimens’ specific heat capacity values present the increasing trend. The 25 %Fe–15 %Co–60 %Cu specimens have negative enthalpy value at 10 and 20°C/min heating rate but positive values at 30 °С/min. For the specimens with lower Cu content, the enthalpies are always positive. It is established that both the specific heat capacity and enthalpy are larger when at higher heating rates. The activation energy of the 65 %Fe–15 %Co–20 %Cu specimens is 10 times higher than that of the 25 %Fe–15 %Co–60 %Cu specimens and the 45 %Fe–15 %Co–40 %Cu specimens.